The Development of Community Education and Language: An Exploration of the Riam Panjang in the Interior of West Kalimantan - Buti, Sri; Yusriadi, Yusriadi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2023)
The study of the implications of education on societal change is important in social and educational contexts. This study was conducted in that context; it aims to describe how the implications of citizens ' education on their language. Data were collected in Riam Panjang Village, Kapuas Hulu. The place is more in the upper reaches of the Kapuas River, about 400 km from Pontianak, the capital of West Kalimantan province. Data were collected through interviews and observation. Data analysis was conducted with the approach of Cresweell (2015). In conclusion, the rapidly growing education in Riam Panjang has transformed monolingual societies into multilingual ones in the last 30 years. The community of speakers who initially spoke one language (monolingual), namely Malay Ulu Kapuas, became a bilingual community that spoke other Malay languages (Indonesian, Pontianak language), as well as several other languages. Changes are contributed by the need for interaction of society with the outside world, as a result of development and globalization. The implication of this study is the need for specific policies of decision makers about regional language retention. If there is no specific policy, it is feared that regional languages will become extinct, and that means part of the wealth of communal knowledge will also be extinct.